Role of Prunus Spinosa in Cases of UTI (Homoeopathy for All, 2024)
Urinary tract infections (UTI) are  among the most prevalent infectious  GLVHDVHV  ZLWK D VXEVWDQWLDO ¿QDQFLDO  burden on society. These are  among the most common bacterial  infections in humans, both in the  community and hospital settings and  have been reported in all age groups  in both sexes. A case series of 4  patients diagnosed with UTI with  history of recurrence/incomplete  relief after conventional treatment  and complete resolution in response  to homoeopathic medicine Prunus  spinosa is presented.
Keywords: UTI; RUTI; Prunus spinosa; UTISA; homoeopathy